Proceedings of the First International Conference on Science, Technology, Engineering and Industrial Revolution (ICSTEIR 2020) 2021
DOI: 10.2991/assehr.k.210312.088
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers’ Readiness and Emotional Presence on Online Teaching Data in a Malaysian University During COVID-19

Abstract: This article presented a survey data on the lecturers' perception on online teaching during the COVID-19 outbreak. The study adopted a quantitative approach with an open-ended survey questionnaire to establish lecturers' readiness and their emotional presence in adopting 100% online teaching from home. The questionnaire consists of two sections, quantitative and qualitative. As for the quantitative section, the data comprised of demographic characteristics of research respondents and the qualitative section co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…With the sudden pandemic that shifted to online learning, challenges arose among examiners who are not tech-savvy. A study among 180 academicians in Malaysia found that 45.5% of respondents did not have a suitable workplace at home, where 92 respondents had data plans below 40 GB despite the majority having internet data connection at home (Ahmad Tajuddin et al, 2021). Intensive training sessions were conducted for the examiners to help them familiarise themselves with the platform and mechanism of the virtual OSCE.…”
Section: Human Resourcesmentioning
confidence: 99%
“…With the sudden pandemic that shifted to online learning, challenges arose among examiners who are not tech-savvy. A study among 180 academicians in Malaysia found that 45.5% of respondents did not have a suitable workplace at home, where 92 respondents had data plans below 40 GB despite the majority having internet data connection at home (Ahmad Tajuddin et al, 2021). Intensive training sessions were conducted for the examiners to help them familiarise themselves with the platform and mechanism of the virtual OSCE.…”
Section: Human Resourcesmentioning
confidence: 99%
“…Obviously, although teachers play the prevalent role in controlling their own emotions, external factors should also be taken into consideration. For example, institutional support, such as training and infrastructure, may also influence teachers' readiness and emotional experiences (Tajuddin et al, 2021).…”
Section: Literature Review Teachers' Emotionsmentioning
confidence: 99%
“…From China [6] to Palestine [7] teachers' efforts at fostering connection and presence were considered a key predictor of student engagement when learning online. To foster engagement, a number of studies promoted the need for interconnectedness online [8], through the creation of socially constructed communities [9], and through small group work learning [2].…”
Section: Literature Reviewmentioning
confidence: 99%